MEMAHAMI PENGALAMAN KOMUNIKASI ORANG TUA – ANAK KETIKA MENYAKSIKAN TAYANGAN ANAK-ANAK DI MEDIA SOSIAL TIK TOK - Abdulhakim Arrofi; Nurul Hasfi (Interaksi Online, 2019)
This study aims to understand how the parent-child communication experience when watching children's shows on social media Tik Tok. This research is motivated by the emergence of a social media phenomenon that is widely used by the community, Tik Tok, whose presence makes various types of controversies in the form of video content that is not suitable for consumption by children. This research was conducted through a phenomenology approach and with a qualitative descriptive method. The main theory used in this study is the Phenomenology Theory of Alferd Schutz. Data collection techniques were carried out by in-depth interviews with 8 informants. The results of this study found that parents understand that Tik Tok social media contains negative content for children. In addition, parents can give examples of negative content, namely vulgar shows, erotic, lipsync adult songs. In communicating with children about shows in Tik Tok parents do it based on two motives namely future motives (in order motive) and past motives (because motive). Future motives in the form of motives to be achieved, namely aiming that children do not do negative things, understand the boundaries in social media and foster the creative nature of children in the future, in doing that communication parents do it by discussing and proposing appropriate shows age of child. Past motives are the reason for parents to communicate with children. Parents' experience derived from an understanding of social media Tik Tok makes parents communicate the programs on social media Tik Tok and apply actions in the form of regulations, among others, by limiting time to access, accompanying children and discussing shows with children.